Antecedents of Attitude and Intention towards female entrepreneurs in Jordan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Entrepreneurial intentions' antecedents help us understand, explain, and forecast entrepreneurial activity better. Research confirms that intentions play an important role in the decision to start a new firm. The aim of this study is explanatory research of entrepreneurial education, access to finance, government policy, and attitude of Jordanian female entrepreneurs towards entrepreneurial intention. A conceptual framework is derived and tested in the context of female small business owners through structural equation modeling. Planned behavior theory is the key theoretical framework used in this exploratory study which hypothesizes that entrepreneurial education, access to finance, government policy, and attitudes have a positive effect on entrepreneurial intentions which in turn lead to entrepreneurial activity. We test our hypothesis amongst Jordanian businesswomen who engaging with economic institutions, support groups, businesswomen groups, and individuals and currently engaging in entrepreneurial activity.The main finding is that attitudes have the strongest and positive effect on entrepreneurial intentions. Entrepreneurial education and government policy are found to significantly contribute to entrepreneurial intentions. Our research contributes to the study of entrepreneurship as it uses the theory of planned behaviour in the context of the Jordan amongst active female entrepreneurs. Implications are discussed for theory and practice.